Logistics Services Sector and Economic Recession in Greece: Challenges and Opportunities - Dimitrios Folinas; Naoum Tsolakis; Dimitrios Aidonis (Logistics)
The recent economic recession in Greece has had a detrimental impact on all national business activities, with the logistics industry being one of the most affected sectors primarily due to the significant decrease in market demand for goods and services. In this regard, the aim of this research is to identify key challenges and prospects for the Greek logistics services industry stemming from the recent economic crisis era through a critical literature taxonomy, a semantic analysis of the reviewed articles, and a questionnaire-based survey involving 140 executives from the third-party logistics sector. In principal, the recent economic crisis is reported to have significantly affected logistics service providers, thus further imposing structural reforms in the industry. The reduction in operating profits of transport companies is noticeable with the onset of the economic crisis, specifically in 2016. Nevertheless, logistics executives are optimistic regarding the near future, provided that educated and informed strategic management decisions are made and inventive business practices are embraced.